Wewnętrzna podróż do Demiana – archetypy jungowskie w "Demianie" Hermanna Hessego - Szyszka, Kamila (Acta Neophilologica, 2021)
This paper analyses Hermann Hesse’s novel Demian in the context of Jungian psychological archetypes. Hesse’s in-depth interest in psychoanalysis is evident in his works. The content of Demian was particularly influenced by Carl Jung’s psychoanalytic concepts since the author had undergone Jungian psychoanalytic treatment prior to writing the novel. The paper claims that most major characters in Demian are in fact personifications of Jungian archetypes of: self, shadow, and anima. It is indicated that it would be impossible to understand the novel properly without basic knowledge of these archetypes. It is demonstrated that Demian is in fact a novel dealing with the inner psychological development of an individual even though it may not appear so if the characters and events are interpreted literally.